Building resilience of health systems to climate change in Pacific Least Developed Countries: implementation science - Kristie Ebi, ProfPhD; Chris Boyer, MPH (The Lancet Planetary Health, 2019)
Background: The Pacific Least Developed Countries (LDCs)—Kiribati, the Solomon Islands, Tuvalu, and Vanuatu—are among the countries most vulnerable to climate variability and change. Key climate change risks include loss of livelihoods, coastal settlements, infrastructure, ecosystem services, and economic stability; and interaction of sea level rise with high-water-level events, threatening low-lying coastal areas. These risks result in increased health impacts, including deaths and injuries from extreme events (eg, heatwaves, storms, and floods); increased risks of infectious diseases (including food-borne, water-borne, and vector-borne); food insecurity and malnutrition; and diffuse impacts from loss of livelihoods and migration. The young, older adults, women of reproductive age, and people with disabilities are most vulnerable. Methods: Building resilience to climate change requires that these countries develop National Climate Change and Health Action Plans, including Vulnerability and Adaptation assessments. Findings: Temperature, precipitation, and extreme weather events can influence the incidence, geographic distribution, and seasonality of climate-sensitive health outcomes. In addition, many hospitals and community health centres are highly vulnerable to cyclones, floods, storm surges, sea level rise, and disturbances in water supply caused by drought or salination of aquifers. The capacity to provide health services, particularly in emergency situations, is substantially affected if buildings and essential supplies and amenities are damaged. The majority of health facilities are not resilient to climate-induced pressures in terms of structural, non-structural, and functional safety. Interpretation: The most effective measures to reduce vulnerability are (i) short-term programmes that implement and improve basic public health measures, including the provision of safe water and improved sanitation, secure essential health care, and increase capacity for disaster preparedness and response; and (ii) longer-term programs that enhance national health systems and institutions with climate change-related risks integrated into health governance, strengthen health information management systems, and ensure effective and accessible delivery of health services. Funding: Least Developed Countries Fund under the United Nations Framework Convention on Climate Change.